A Descriptive Study to Assess the General Well-Being among Married Women with Domestic Abuse in Selected Community Area of Kanchipuram District, Tamil Nadu (Medico Legal Update, 2020)
Intimate partner violence is any act of gender-based violence that results in, or is likely to result in, physical,sexual, or mental harm or suffering to women, including threats of such acts, coercion or arbitrary deprivationof liberty, whether occurring in public or in private life. A study was conducted to assess IPV and to findthe association between IPV and selected demographic variables. Majority of the samples experienced IPV.Duration of marital life, age of the woman, spouse’s occupation, family monthly income were associatedwith IPV.